2016
DOI: 10.1007/s12298-016-0361-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in Mucuna species of India using randomly amplified polymorphic DNA and inter simple sequence repeat markers

Abstract: Genus Mucuna which is native to China and Eastern India comprises of perennial climbing legume with long slender branches, trifoliate leaves and bear green or brown pod covered with soft or rigid hairs that cause intense irritation. The plants of this genus are agronomically and economically important and commercially cultivated in India, China and other regions of the world. The high degrees of taxonomical confusions exist in Mucuna species that make authentic identification and classification difficult. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Many studies conducted on other genus revealed similar results with insufficient molecular studies of Anthemideae (Matousek et al, 2007;Garcia et al, 2010;Riggins and Seigler, 2012). Similar results were obtained by other authors (Riggins and Seigler, 2012;Patil et al, 2016;Higgins et al, 2016;Kumar et al, 2016).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Many studies conducted on other genus revealed similar results with insufficient molecular studies of Anthemideae (Matousek et al, 2007;Garcia et al, 2010;Riggins and Seigler, 2012). Similar results were obtained by other authors (Riggins and Seigler, 2012;Patil et al, 2016;Higgins et al, 2016;Kumar et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…RAPD is a PCR-based technique developed by (Williams et al, 1990) and (Welsh and McClelland, 1990) which employs decamer random primers, for amplifying random DNA fragments from genomic DNA without any prior knowledge of the genomic sequence of any organism. Recently, several studies have used this tool to measure the levels and patterns of variations within different plants (Abd El-Ghani and El-Sawaf, 2004;Sarwat et al, 2008;Thendral et al, 2010;Hammadi and Qari, 2012;Ismail et al, 2016;Lu et al, 2016;Patil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, three different kinds of markers namely RAPD, ISSR and RAMP markers were employed to determine the phylogenetic relationship in C. nutans species. RAPD has been successfully applied in genetic variation investigations of Mucuna pruriens due to its usefulness as an informative and cheap tool for plant breeding programs (Patil et al 2016). There are also many researchers using these markers as one of their techniques to study the genetic diversity of their desired plant species (Desai et al 2015;Kumar et al 2009Kumar et al , 2010Mei et al 2015;Patel et al 2015;Patil et al 2016;Pu et al 2009;Saleh 2015;Zhao et al 2013;Zhao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies concentrated on genetic diversities based on polymorphic markers but intraspecific diversities among Mucuna pruriens species based on barcode markers are least attempted. Patil and coworkers evaluated the genetic diversity of Indian Mucuna species using RAPD and ISSR markers and reported the highest genetic diversity among the Mucuna pruriens species and this study conclused that DNA barcode based approach is necessary to understand the phylogenetic relationships among the Mucuna species (Patil et al 2016). In the recent years, DNA barcode markers like ITS, matK and trnHpsbA are popular in understanding the intraspecific diversities among the closely related plant groups.…”
Section: Resultsmentioning
confidence: 77%